Gene regulation and signaling transduction in mediating the self-renewal, differentiation, and apoptosis of spermatogonial stem cells - Cai-Mei He; Dong Zhang; Zuping He (Asian Journal of Andrology)
Infertility has become one of the most serious diseases worldwide, and 50% of this disease can be attributed to male-related factors. Spermatogenesis, by definition, is a complex process by which spermatogonial stem cells (SSCs) self-renew to maintain stem cell population within the testes and differentiate into mature spermatids. It is of great significance to uncover gene regulation and signaling pathways that are involved in the fate determinations of SSCs with aims to better understand molecular mechanisms underlying human spermatogenesis and identify novel targets for gene therapy of male infertility. Significant achievement has recently been made in demonstrating the signaling molecules and pathways mediating the fate decisions of mammalian SSCs. In this review, we address key gene regulation and crucial signaling transduction pathways in controlling the self-renewal, differentiation, and apoptosis of SSCs, and we illustrate the networks of genes and signaling pathways in SSC fate determinations. We also highlight perspectives and future directions in SSC regulation by genes and their signaling pathways. This review could provide novel insights into the genetic regulation of normal and abnormal spermatogenesis and offer molecular targets to develop new approaches for gene therapy of male infertility.